Measurement of GPS Derived Precipitable Water Vapour (PWV) in Low and High Altitudes in Nepal - Saud, Kuber; Sah, Nabin; Ghimire, Basu Dev; Khadka, Balaram; Nagarkoti, Shreeram; Pokheral, Aakash; Chapagain, Narayan Prasad (Journal of Kathmandu BernHardt College, 2024)
The study of Precipitable Water Vapour (PWV) using satellite data and ground-based observation is crucial for understanding hydrological processes, atmospheric circulation, and weather systems. It is considered the most prominent greenhouse gas in the Earth’s atmosphere. It is highly variable in both space and time across the Earth. Precipitable Water Vapor is a measure of the total amount of water vapour present in a vertical column of the atmosphere from the Earth’s surface to the top of it. This study investigates the potential atmospheric water vapour column at high (JMSM)and low(GRHI) to understand water vapour dynamics. To investigate precipitable water vapour, GNSS/GPS data were downloaded from UNAVCO SAGE. The downloaded data were processed and analyzed using GAMIT/GLOBK software which is a comprehensive GPS analysis package developed at the Massachusetts Institute of Technology (MIT), the Harvard-Smithsonian Center for Astrophysics (CfA), and the Scripps Institution of Oceanography (SIO). The main purpose of this software is to process data for Atmospheric science. This paper’s findings investigate the PWV amount in high and low altitudes over a year. Our finding shows that there is a significant difference in PWV levels between the two stations, with low-altitude areas exhibiting higher humidity and precipitation during the monsoon season, while high altitudes show reduced water vapour concentrations influenced by surrounding climatic variation.